PENGARUH VIDEO PEMBELAJARAN DI MASA PANDEMI COVID 19 TERHADAP MOTIVASI PERKULIAHAN DAN HASIL KULIAH STATISTIK DESKRIPTIF PJKR UNIVESRSITAS PGRI MAHADEWA INDONESIA - I Made Darmada (Widyadari : Jurnal Pendidikan, 2021)
This research is a quantitative study using a quasi-experimental method, patterned "Single Factor Independent Group Design". The population was the 6th semester students of PJKR PGRI Mahadewa University Indonesia from 4 classes with a total population of 123, and samples by random sampling, obtained 2 classes, one class was used as an experimental class and one control class. Data were analyzed using MANOVA assisted by SPSS 25.00. Research Results: First, the lecture motivation among students who take scientific learning assisted by video learning is better than students who take scientific learning without assisted learning video (Sig <0.05). Second, the results of the Descriptive Statistics course between students who take scientific learning assisted by video learning are better than students who take scientific learning without assisted learning video (sig <0.05). Third, Simultaneously lecture motivation and lecture results Descriptive statistics between students who take scientific learning assisted by video learning is better than students who take scientific learning without assisted learning video (F <0.05). Based on these findings, it can be concluded that scientific learning assisted by video learning has an effect on lecture motivation and descriptive statistics lecture outcomes